Tents encampment along the White Pass Trail near Log Cabin, ca. 1898 - Curtis, Asahel, 1874-1941 (1898)
Handwritten on verso: Near Log Cabin BC on White Pass Trail from Skagway Alaska. PH Coll 519. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number